2002
DOI: 10.2337/diacare.25.1.245
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Blood Glucose Monitoring in Relation to Glycemic Control in Patients With Type 2 Diabetes

Abstract: A randomized study Placebo Low dose High dose n 6 6 6 Fasting plasma glucose (mmol/l) 8.2 Ϯ 0.2 8.8 Ϯ 0.4 8.3 Ϯ 0.6 8.4 Ϯ 0.3 8.4 Ϯ 1.1 7.2 Ϯ 0.4* Fasting plasma insulin (pmol/l) 8.7 Ϯ 1.7 8.3 Ϯ 1.6 13.4 Ϯ 2.5 8.7 Ϯ 1.2 9.0 Ϯ 1.8 13.2 Ϯ 2.5 Total cholesterol (mmol/l) 5.69 Ϯ 0.23 6.05 Ϯ 0.31 4.97 Ϯ 0.21 5.66 Ϯ 0.31 5.68 Ϯ 0.34 4.45 Ϯ 0.18* LDL cholesterol (mmol/l) 3.72 Ϯ 0.23 4.11 Ϯ 0.28 3.12 Ϯ 0.16 3.78 Ϯ 0.41 3.80 Ϯ 0.28 2.72 Ϯ 0.16* HDL cholesterol (mmol/l) 1.40 Ϯ 0.10 1.27 Ϯ 0.10 1.16 Ϯ 0.05 1.42 Ϯ 0.16 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Less frequent monitoring was also effective. A recent response letter to Diabetes Care also reported a positive association between regular SMBG and consistent discussions about the monitoring with a health care provider and glycemic control: HbA 1c levels significantly improved with regular monitoring (12). Theoretically, meal-related SMBG could lead to better compliance with diet or other treatment interventions, eventually resulting in better glycemic regulation.…”
Section: T He Uk Prospective Diabetes Studymentioning
confidence: 99%
“…Less frequent monitoring was also effective. A recent response letter to Diabetes Care also reported a positive association between regular SMBG and consistent discussions about the monitoring with a health care provider and glycemic control: HbA 1c levels significantly improved with regular monitoring (12). Theoretically, meal-related SMBG could lead to better compliance with diet or other treatment interventions, eventually resulting in better glycemic regulation.…”
Section: T He Uk Prospective Diabetes Studymentioning
confidence: 99%
“…Despite a documented increase in use of SMBG (3) in response to expert opinion and exhortations of the American Diabetes Association (4), no appreciable corresponding cost reduction in supplies has occurred, leading to an expanding economic burden on health care systems worldwide. Therefore, it is not surprising that the need for routine SMBG in diabetes management is increasingly being questioned (5)(6)(7)(8).…”
Section: Point: Self-monitoring Of Blood Glucose In Type 2 Diabetic Pmentioning
confidence: 99%
“…Although SMBG as a tool for achieving glycemic targets is considered to be effective in type 1 diabetes (9,10) and type 2 patients on insulin (11,12), questions have been raised about the need for its use (5)(6)(7)(8) in the majority of potential users, non-insulin-treated type 2 diabetic (NIT-DM) patients. Those challenging the use of SMBG in NIT-DM patients generally cite two major problems in support of their position: the enormous cost of supplies and the lack of evidence for effectiveness in this group.…”
Section: Point: Self-monitoring Of Blood Glucose In Type 2 Diabetic Pmentioning
confidence: 99%
“…While an early study by Harris 24 concluded that SMBG has no role in the management of T2DM management, Blonde and colleagues 25 observed that SMBG has a substantial affect on diabetes care when the role of the HCP is considered. In essence, their position is that rather than simply collecting blood glucose data, it is the effective use of blood glucose information for making clinical decisions that leads to improvements in diabetes control.…”
Section: Health Care Provider Utilizationmentioning
confidence: 99%